Timing analysis - from predictions to certificates - Nuno Gaspar (2010)
In real-time systems, timing constraints must be satisfied in order to guarantee that deadlines will be met. The calculation of each task?s worst-case execution time (WCET) is a prerequisite for the schedu- lability analysis, and hence of paramount importance for real-time sys- tems. However, an accurate prediction can be difficult if the underlying hardware architecture possesses features like caches and pipelines. In this paper we report our work in progress project on ACCEPT, an Abstraction-Carrying CodE Platform for Timing validation. Our ap- proach counts on information gathered at source-code level (e.g. loop bounds, infeasible paths), defined by annotations that also express the intended timing behaviour. Furthermore, in the context of mobile code safety and in order to minimize the trusted computing base, we produce a checkable certificate whose validity entails compliance with the calcu- lated WCET.